Designing Educational Attractions Based on Local Wisdom - Ellyn Normelani; Selamat Riadi; Muhammad Efendi; Rendya Adi Kurniawan; Rizky Nur Hakimah (Social Studies Conference Proceedings, 2022)
This study aims to identify the natural and cultural potential of the Dayak Loksado indigenous people and to design environmental and educational tourism activities that are synergized with the values ​​of local community wisdom. Data were collected through field observations, interviews, and document reviews. The results of this study reveal that Loksado has natural and cultural potential to be packaged as an educational and ecotourism destination. Natural potential includes panoramas in the form of waterfalls, protected forests, hills, cultivation areas, rivers, and the Dayak Loksado indigenous people’s culture.